2018
DOI: 10.1002/lary.27528
|View full text |Cite
|
Sign up to set email alerts
|

When to replace legacy cochlear implants for technological upgrades: Indications and outcomes

Abstract: Objective To determine indications, surgical efficacy, and audiologic outcomes of replacing Advanced Bionics Clarion C1.2 internal devices (Advanced Bionics, LLC, Valencia, CA) as a means of technology upgrade. Study Design Retrospective review, case series. Methods Ten patients were initially implanted as a child (mean age = 3.87 years) and underwent cochlear implant reimplantation (CIR) with current Advanced Bionics internal device as a young adult (mean duration of implant use = 15.66 years). Demographic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…This is an encouraging result, as patients with CI offering good performances seemed not to be at risk of significant decrement after reimplantation. This outcome favors the feasibility of replacing the old CI for technological upgrading without risking audiological performance decrement [ 12 ]. However, we observed that patients with suboptimal speech rehabilitation presented a median decrease of −19% in their performances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an encouraging result, as patients with CI offering good performances seemed not to be at risk of significant decrement after reimplantation. This outcome favors the feasibility of replacing the old CI for technological upgrading without risking audiological performance decrement [ 12 ]. However, we observed that patients with suboptimal speech rehabilitation presented a median decrease of −19% in their performances.…”
Section: Discussionmentioning
confidence: 99%
“…Device malfunctions can be separated into hard device failure (acute and complete loss of connection between the external and internal device with abnormal electrophysiological testing) and soft device failure (audiological performance decrement and exclusion of detectable hardware or software-related causes) [ 9 , 10 ]. More recently, the indication of reimplantation for technological upgrading of older implants has been discussed [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some articles did not attempt to define cochlear reimplantation at all ( Bhadania et al, 2018 ; Batuk et al, 2019 ). “Reimplantation/re-implantation” are often used to mean CI reimplantation, and “reinsertion/replacement” are also used in the same context ( Desoyer and Burian, 1985 ; Parisier et al, 1991 ; Holcomb et al, 2018 ; Lane et al, 2019 ). However, there existed confusion and genericity between “revision” and “reimplantation” in many studies ( Lassig et al, 2005 ; Rivas et al, 2008 ; Hwang et al, 2019 ).…”
Section: Part Ii: Current Deficiencies and Future Research Directionsmentioning
confidence: 99%
“…Another main outcome measure is speech perception in noise. This can be assessed at fixed signal‐to‐noise ratios 5 , 6 , 7 for accessing percent correct scores or at variable signal‐to‐noise ratios by adaptively administering a speech reception threshold (SRT) test. 8 , 9 , 10 In noisy listening situations, CI recipients experience a larger deterioration of speech perception than normal hearing subjects 11 , 12 accompanied by a considerable variability in quiet as well in noise.…”
Section: Introductionmentioning
confidence: 99%
“…During the last two decades a range of dedicated signal processing algorithms for CI sound processors such as conventional beamformer, dynamic range optimization, and spatial post‐filter technologies were introduced. Each has aimed to improve the speech perception in a specific listening situation like speech in quiet, 10 , 22 speech in noise, 7 , 17 speech in spatially distributed noise, 2 , 23 , 24 , 25 and speech in fluctuating competing signals. 11 , 26 , 27 The most recent sound processor generation from Cochlear (CP1000) offers a dedicated preprocessing technology for spatially distributed fluctuating competing signals, enabling CI recipients to better understand conversations in one of the most challenging listening situations, 11 commonly referred to as cocktail party noise.…”
Section: Introductionmentioning
confidence: 99%